Публічна безпека через призму основних загроз: феноменологічний вимір - Сокуренко, В. В.; Sokurenko, V. V.; Valerii Sokurenko (Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 100-108, 2017)
У статті проаналізовано вірогідні загрози публічній безпеці в Україні. Виокремлено та охарактеризовано п’ять основних груп загроз публічній безпеці: політичні, природничі, техногенні, антропогенні, криміногенні. Запропоновано авторське визначення поняття «загрози публічній безпеці».

Threats to public safety - the concept is as comprehensive as the very public safety, because the content of the latter is largely a reflection of the dangers emerging as risk factors equal to the system’s state – perceiving subject: a man, social group, society in the whole. The author of the article has listed possible threats to public safety in Ukraine. More fruitful approach seems to be the analysis of threats to public safety, the basis of which is not within the area of their reconstitution, but their nature, content and direction of destructive factors of socio-dynamics. On this basis we believe it is possible to determine the following threats to public safety. 1. Political threats that may be divided into external (geopolitical, regional) and internal (caused by internal political opposition). 2. Natural threats. These should include dangerous geological (earthquakes, land or bowels degradation, avalanches and other lithospheric phenomena), meteorological (weather, air flows and other atmospheric phenomena), hydrological (sea waves, runoff modes, floods, tsunamis, freezing, the change of water resources’ state and other hydrospheric phenomenon), biological (yield, natural fires, massive destruction of crops and animal diseases or pests, the change of the biosphere and other phenomena in flora and fauna), biomedical (human diseases) cosmological (the state and movement of celestial bodies, gas emissions, all phenomena in the space), physical and chemical (the change of the state of the microworld). 3. Man-made threats that are in the danger of emergencies, accidents associated with the operation of technical devices of different nature and degree of difficulty by a human being: nuclear power plants, hydrological structures, construction and other industrial equipment, etc. 4. Anthropogenic threats arise, develop and are implemented: a) in the depths of human-driven techno-sphere, which, in particular, embodied in the settlements infrastructure, transport communications (systems of automobile, aviation, water, pipelines transport); b) in the information environment, except politically determined information phenomena; c) in the corruption within state agencies; d) in the social tension as a background psychological phenomenon of the socio-dynamics; d) in the socio-economic conflicts and so on. The list of threats to public safety is not and can not be exhaustive because of the dynamism of social changes, progress of, technical ideas, not socially equal, difficult in forecasting consequences of the bifurcation in the conditions of social systems: economic, political, cultural and psychological, legal and their institutional often integrated, interrelated substances of various degree of resistance.

В статье проанализированы возможные угрозы публичной безопасности Украины. Выделены и охарактеризованы пять основных групп угроз публичной безопасности: политические, природные, техногенные, антропогенные, криминогенные. Предложено авторское определение понятия «угрозы публичной безопасности».
Public safety through the prism of the main threats: phenomenological dimension
Публичная безопасность через призму основных угроз: феноменологическое измерение
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; публічна безпека; загрози; політична загроза; природнича загроза; техногенна загроза; антропогенна загроза; криміногенна загроза; public safety; threats; political threat; natural threat; technological threat; anthropogenic threat; criminal threat; публичная безопасность; угроза; политическая угроза; природная угроза; техногенная угроза; антропогенная угроза; криминогенная угроза